2017
DOI: 10.11648/j.sjph.20170503.22
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices on Malaria Prevention and Control Among Private Security Guards Within Kaduna Metropolis, Kaduna State-Nigeria

Abstract: An understanding of knowledge, attitudes and practices among different populations such as security guards temporarily outside the home due to occupational reasons are key determinants for policy makers in designing malaria prevention and control interventions. A survey on knowledge, attitudes and practices (KAP) on malaria prevention and control was conducted among two hundred and sixty-one (261) private security guards in Kaduna Metropolis, Kaduna State-Nigeria using a structured questionnaire. Data were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
5
8
1
Order By: Relevance
“…This difference could be due to discrepancies in study design, study period, and population. In addition, these discrepancies could also be attributable to that fact employees received bed nets at work as a result of health promotion policies implemented in enterprises where they work as reported previously in Nigeria [ 9 ]. It is plausible that the true proportion of employees using ITNs could be lower than that estimated in the present study since a self-report-based approach was used to determine the rate of ITN use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference could be due to discrepancies in study design, study period, and population. In addition, these discrepancies could also be attributable to that fact employees received bed nets at work as a result of health promotion policies implemented in enterprises where they work as reported previously in Nigeria [ 9 ]. It is plausible that the true proportion of employees using ITNs could be lower than that estimated in the present study since a self-report-based approach was used to determine the rate of ITN use.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria control is changing in several endemic countries where community/individuals adhesion to control and prevention measures is placed at the core of control policies, with a growing interest in health education through the understanding of knowledge, attitudes, and practices (KAP) towards malaria and its control [ 9 ]. KAP studies are also essential in establishing epidemiological and behavioral baselines in monitoring programs against malaria [ 9 ]. In fact, a person who has poor KAP towards a given disease may probably be reluctant to use some of the preventive measures and communicate the information on their positive effects on the control of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from malaria knowledge, attitudes, and practices (KAP) studies reported that misconceptions on malaria transmission and risk factors still exist with adverse impact on malaria control programmes [11, 12]. Findings from a study conducted by Singh et al in rural areas of Northern Nigeria revealed that although knowledge about malaria prevention measures was high (90%), it was poorly reflected in their practices (16%) [13].…”
Section: Introductionmentioning
confidence: 99%
“…For progress to be made, all aspects of knowledge which can be achieved through education and training are to be considered. Among these are raising awareness of the disease and its associated preventive measures, deepening the understanding of the coherent dynamic relation of awareness and wisdom (which is application of skills required according to exigencies of time) and keeping on refining the acquired conception or information through the mechanisms founded within localities [18,19].…”
Section: Study Implications and Conclusionmentioning
confidence: 99%